Sikap Warga Komunitas Lokal terhadap Pembangunan Pembangkit Listrik Tenaga Panas Bumi (PLTP) (Suatu Studi pada Warga Desa Ngebel Kecamatan Ngebel Kabupaten Ponorogo) - Ulum, Mochamad Chazienul (Jurnal Ilmiah Administrasi Publik, 2018)
One of the regions in East Java that has the potential as a major electricity producer is Ponorogo Regency. The Government of Ponorogo Regency itself through the Regional Regulation (Perda) of Ponorogo District Number 1 of 2012 concerning the Regional Spatial Plan of Ponorogo Regency (2012-2032) has regulated the development of infrastructure to increase electricity productivity by developing Geothermal Power Plants in Ngebel District. This then attracted the attention of domestic investors, namely PT. Darmakarya Energi Bakrie to establish a Geothermal Power Plant (PLTP) in the Ngebel Village area, Ngebel District, Ponorogo Regency. The development that has been planned will be able to run as expected together if it receives a positive response from the community. So it would have been a necessity if planning, implementing, and the results of development should be oriented towards the community, including the local community.